Electroacupuncture as a rapid-onset and safer complementary therapy for depression: A systematic review and meta-analysis - Zhang, Zhinan; Cai, Xiaowen; Liang, Yuying; Zhang, Rui; Liu, Xinyu; Lu, Liming; Huang, Yong (Frontiers in Psychiatry, 2023)
Background: Electroacupuncture (EA) is a promising therapy for depression. However, a comprehensive review of EA for depression is needed. Methods: We conducted a systematic review and meta-analysis in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA 2020) guidelines to evaluate the efficacy and safety of EA for depression. Potentially relevant trials and reviews were searched in MEDLINE, EMBASE, PsycINFO, and CENTRAL from inception to March 2022. EA alone and combined with other therapy were eligible for inclusion. The severity of depression during and after treatment and the number of adverse events were assessed as outcomes. Risk of bias (ROB) evaluation, subgroup analysis, sensitivity analysis, reporting bias assessment, and GRADE system evaluation were also conducted. Results: Thirty-four trials were included. The overall ROB was medium. Low-quality evidence showed that the efficacy of EA was not less than that of antidepressants (EA+selective serotonin reuptake inhibitors (SSRIs) and tricyclic antidepressants (TCAs)) and manual acupuncture (MA). EA and EA+SSRIs had better efficacy than SSRIs alone in decreasing the severity of depression during the early treatment. Moderate-quality evidence also showed that EA and EA+SSRIs were safer than SSRIs alone. Sensitivity analysis was mostly not feasible. Major publication bias was unlikely. Conclusions: These results indicate that the efficacy of EA is not less than that of antidepressants and MA. Moreover, EA and EA+SSRI treatments show a more rapid onset and greater safety than SSRIs. More high-quality trials are needed for further confirmation.